Perkembangan Instrumen Pembelajaran Gambar Pembelajaran Berbasis Luar Negeri Untuk Siswa - Rebecca Suzie Setlight; Ventje Noldy Kalalo; Liberman Hulu; Wimpie Tanojo; Lily Tasim (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2018)
This research purpose to describe factually learning instrument dan characteristics of learning instrument was developed and acquiring products of drawing learning instrument that are valid and effective.The R and D research design used modifications Thiagarajan 3D model consisting of definition phase, design phase and development phase with research subjects are students of fourth grade at Singosari 2 Elementary School were selected by purposive sampling. The results showed are learning instruments in fact still found mismatch content and components. Drawing learning instruments based on outdoor learning that has five syntax, such as: (1) preliminary, (2) exploration, (3) outdoor learning based school environment, (4) elaboration, and (5) presentation. The validation result of learning instruments obtained an average of 3.46, it is include of very valid category. The result of learning instrument trials shows that: (1) measurement creativity is 7.01 an average, (2) percentage student’s activity get 66.87% in active category, (3) percentage student's response of learning implementation get 83,05% in very positive category, and (4) percentage teacher's respons of lesson plan get 85% in very positive category. The final product of the research was in the form of a teacher manual on drawing learning devices based on outdoor learning.